Вы находитесь на странице: 1из 4

Lesson 8: Negative Exponents and the Laws of Exponents

1
Definition: For any nonzero number x ,and for any positive integer n , we define x−n as .
xn

1
Note that this definition of negative exponents says x−1 is just the reciprocal, , of x .
x

As a consequence of the definition, for a nonnegative x and all integers b , we get

1
x−b= .
xb
Exercise 1
1
Verify the general statement x−b=¿ for x=3 and b=−5.
xb

Exercise 2
What is the value of ( 3 ×10−2 )?

Exercise 3
What is the value of ( 3 ×10−5 )?

Exercise 4 deleted by C Barnes


For Exercises 5–10, write an equivalent expression, in exponential notation, to the one given, and simplify as much
as possible.

Exercise 5 Exercise 6
5−3 =¿ 1
=¿
89

Exercise 7 Exercise 8
3 ∙2−4=¿ Let x be a nonzero number.

x−3=¿
Exercise 9 Exercise 10
Let x be a nonzero number. Let x , y be two nonzero numbers.
1 x y −4=¿
=¿
x9

Exercise 11 Exercise 12
192 1716
=¿ =¿
We5 accept that for nonzero numbers x and y and all integers
19 17−3a and b ,
x a ∙ x b=x a +b
a
( x b ) =x ab
( xy )a=x a y a.
We claim

x a a−b
¿x for all integers a , b .
xb

x a xa
()
y
= a
y
for any integer a .

Exercise 13
If we let b=−1 in (11), a be any integer, and y be any nonzero number, what do we get?

Exercise 14
−4
7 7−4
()
Show directly that
5
=
5−4
.

Problem Set

1. Compute: 33 ×32 ×31 ×30 ×3−1 × 3−2=¿


Compute: 52 ×510 × 58 ×50 ×5−10 ×5−8=¿
Compute for a nonzero number, a : a m × an ×a l × a−n ×a−m ×a−l × a0=¿
8
2. Without using (10), show directly that ( 17.6−1 ) =17.6−8.

n
3. Without using (10), show (prove) that for any whole number n and any positive number y , ( y −1 ) = y−n.

2.8−5 −12
7 ¿ 2.8
4. Without using (13), show directly without using (13) that .
2.8

Exit Ticket

Write each expression in a simpler form that is equivalent to the given expression.

1. 7654 3−4=¿

2. Let f be a nonzero number. f −4 =¿

3. 671 ×28796−1=¿

4. Let a , b be numbers (b ≠ 0). a b−1=¿

1
5. Let g be a nonzero number. =¿
g−1

Equation Reference Sheet

For any numbers x , y ¿ in (4 ) and y ≠ 0 in (5)] and any positive integers m , n , the following holds:
x m ∙ x n=x m +n (1)

n
( x m ) =xmn (2)

( xy )n=x n y n (3)

xm m −n
n
=x (4 )
x

x n xn
()
y
= n
y
(5)

For any numbers x , y and for all whole numbersm , n , the following holds:

x m ∙ x n=x m +n (6 )

n
( x m ) =xmn (7 )

( xy )n=x n y n (8 )

For any nonzero number x and all integers b , the following holds:

1
x−b= (9 )
xb

For any numbers x , y and all integers a , b , the following holds:

x a ∙ x b=x a +b (10)

a
( x b ) =x ab (11)

( xy )a=x a y a (12)

x a a−b
=x x≠0 (13)
xb

x a xa
()y
= a
y
x,y≠0 (14 )